Analysis of Risk Factors on the Performance of Tuberculosis Control Program Officers in the Working Area of the Lubuk Kambing Health Center, Jambi, Indonesia - Situmorang, Immanuel; Lukman Hakim; Christina Roos Etty (Community Medicine and Education Journal, 2024)
Indonesia is ranked 2nd in the country with the highest burden of tuberculosis (TB). In Jambi, the detection rate for pulmonary TB cases is still low (19%), and at the Lubuk Kambing Health Center, it only reaches 53%. This study aims to analyze the factors associated with the low rate of TB case detection in the Lubuk Kambing Health Center working area. Cross-sectional research design with 65 respondents. Data analysis uses logistic regression. There is a relationship between level of knowledge, motivation, workload, training, length of service, availability of TCM (molecular rapid test) facilities, active screening of pulmonary TB suspects, honorarium, family support, and evaluation of TB prevention and control officers and TB cadres with low detection capabilities d TB in the Lubuk Kambing Health Center working area. Availability of facilities is the dominant factor related to the low number of TB cases in the Lubuk Kambing Health Center working area. Efforts to increase knowledge, motivation, training, length of service, active screening, honorarium, and family support, as well as providing TCM facilities and regular evaluations, need to be carried out to increase the TB case detection rate.